MARTABAT TOKOH DALAM KUMPULAN CERPEN HIKAYAT KAMPUNG ASAP KARYA MUSA ISMAIL - Rita Susanti; Elmustian Elmustian; Syafrial Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study is a step in understanding dignity. Dignity is oftenlinked with power, rank and position, position, blood ancestry and theenvironment, and property titles. Dignity is also often correlated with agood name, dignity, honor and self-esteem a person, group, or specificcommunity groups. Dignity or self-esteem can be grouped in three areas,namely 1. Dignity is based, namely the individual views of the abilities,status, and role. 2. Social prestige or dignity according to others, theindividual's sense of how others perceive or judge him. 3. Dignity of theideal individual expectations about him or what her future will be. Dignityof character in search based data analysis techniques. The method used isdescriptive method. To obtain information and research data, the authorsuse the technique of documentation or literature. The data were found tobe described by categories dignity. The results of data analysis is based onthe dignity of self-esteem of a character with a level of independence, inthe order of association with the presence of other figures.Keywords: Dignity grouped in three areas, namely the dignity that is based,social dignity and the dignity of the ideal.